Tujuan dari penelitian ini adala Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Sai Apparel Industries Semarang: Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan - Sephia Hanifatulatifa; Kasmari Kasmari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study is to find elements of work environment, work discipline, and work motivation that affect the performance of PT SAI APPAREL INDUSTRIES SEMARANG workers. This is based on observations made about the performance observed in the company's work environment. The sample was taken through the census method from 100 employees of PT SAI APPAREL INDUSTRIES in the production department. To submit the respondent's answer contribution, Google Form was used to collect data. As shown by the results, linear regression testing was widely used in the data collection process to analyze the significant and positive effects on performance attributed to the environment. The significance level of 0.000 is lower than the threshold of 0.05. The results of significant and positive effects on performance are attributed to work discipline with a significance level of 0.000 less than 0.05. As for work motivation, it has a significant value on employee performance with a significance level of 0.004 less than 0.05.